Bacillus subtilis Biofilm Development – A Computerized Study of Morphology and Kinetics - Gingichashvili, Sarah; Duanis-Assaf, Danielle; Shemesh, Moshe; Featherstone, John D. B.; Feuerstein, Osnat; Steinberg, Doron (Frontiers in Microbiology, 2017)
Biofilm is commonly defined as accumulation of microbes, embedded in a self-secreted extra-cellular matrix, on solid surfaces or liquid interfaces. In this study, we analyze several aspects of Bacillus subtilis biofilm formation using tools from the field of image processing. Specifically, we characterize the growth kinetics and morphological features of B. subtilis colony type biofilm formation and compare these in colonies grown on two different types of solid media. Additionally, we propose a model for assessing B. subtilis biofilm complexity across different growth conditions. GFP-labeled B. subtilis cells were cultured on agar surfaces over a 4-day period during which microscopic images of developing colonies were taken at equal time intervals. The images were used to perform a computerized analysis of few aspects of biofilm development, based on features that characterize the different phenotypes of B. subtilis colonies. Specifically, the analysis focused on the segmented structure of the colonies, consisting of two different regions of sub-populations that comprise the biofilm – a central “core” region and an “expanding” region surrounding it. Our results demonstrate that complex biofilm of B. subtillis grown on biofilm-promoting medium [standard lysogeny broth (LB) supplemented with manganese and glycerol] is characterized by rapidly developing three-dimensional complex structure observed at its core compared to biofilm grown on standard LB. As the biofilm develops, the core size remains largely unchanged during development and colony expansion is mostly attributed to the expansion in area of outer cell sub-populations. Moreover, when comparing the bacterial growth on biofilm-promoting agar to that of colonies grown on LB, we found a significant decrease in the GFP production of colonies that formed a more complex biofilm. This suggests that complex biofilm formation has a diminishing effect on cell populations at the biofilm core, likely due to a combination of reduced metabolic rate and increased levels of cell death within this region.